Adaptability constraints of a technically and economically feasible subsurface drainage system in the low-lying acid sulphate soils of Kerala, India - E.K. MATHEW (Irrigation and Drainage Systems 18: 329-346, 2004., 2004)
This paper discusses the introduction of subsurface drainage as a tool to improve rice production in low land areas of acid sulphate soils. Pipe drains with 15 and 30 m spacing were installed in farmers' fields in coastal lowlands of Kerala, India, at Kuttanad. Soil conditions improved within 2 years after the introduction of the subsurface drainage and significantly improved the crop yield. Data collected over a period of 14 years, showed a yield increase of 1.1 t/ha (43) compared to non-drained areas. An economic analysis indicated that subsurface drainage is feasible with a benefit-cost ratio of 2.45, an internal rate of return of 47 and a net present value of Rs 5.17 million. The poor financial status of the farmers, however, is the main constraint for the large-scale adoption of the comparatively capital-intensive subsurface drainage systems in the acid sulphate soils of Kerala.